LncRNA XIST promotes bladder cancer progression by modulating miR-129-5p/TNFSF10 axis - Yu-Lin Kong; Hui-Dan Wang; Meng Gao; Sheng-Zhong Rong; Xiao-Xia Li (Discover Oncology, 2024)
Abstract Background The differential expression, biological function, and ceRNA regulatory mechanism of lncRNA XIST in bladder cancer (BC) were investigated, and its clinical values for the early diagnosis of bladder cancer patients were elucidated. Methods qRT-PCR was employed to detect the expression patterns of lncRNA XIST, miR-129-5p and TNFSF10. The biological functions were measured by CCK8 assay, wound healing assay and transwell assay. Bioinformatics analysis and Dual-Luciferase reporter assay were employed to evaluate the interactions between the lncRNA XIST, miR-129-5p and TNFSF10. Results LncRNA XIST and TNFSF10 were highly expressed and miR-129-5p was low expressed (P < 0.05) in bladder cancer cell line. The depletion of lncRNA XIST inhibited BC proliferation, migration and invasion. Mechanistically, lncRNA XIST could sponge miR-129-5p to regulate TNFSF10 expression in bladder cancer. Furthermore, compared with adjacent tissues, lncRNA XIST and miR-129-5p were lowly expressed (P < 0.01) in bladder cancer tissues, and TNFSF10 was highly expressed (P < 0.001). miR-129-5p and TNFSF10 were associated with the risk of bladder cancer (P < 0.05); the difference in AUC values for the diagnosis of bladder cancer by lncRNA XIST (AUC = 0.739), miR-129-5p (AUC = 0.850) and TNFSF10 (AUC = 0.753) was statistically significant (P < 0.01), and the three genes combined AUC was 0.900, 95%CI was 0.842–0.958 with a sensitivity of 83.3% and specificity of 86.7%. Conclusion XIST, an elevated lncRNA in bladder cancer, inhibition of which could suppress the progression of BC. LncRNA XIST and miR-129-5p could form ceRNA to regulate the expression of TNFSF10.